Effects of feed resources in arid lands on growth performance of local goat kids in southern Tunisia - Ayeb N.; Seddik M.; Hammadi M.; Barmat A.; Atigui M.; Harrabi H.; Khorchani T. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
In southern Tunisia, breeders have developed several strategies to ensure the nutritional requirements of their herds. They profit of the favourable season to establish reserves by harvesting and drying range species and weeds as natural hay called “khortane”. Other dried resources are commonly used such as Stipa tenacissima (gueddim) and olive leaves. The objective of this study was to evaluate the effects of local feed resources on intake and growth performances in goat kids. Twenty seven goat kids of local breed (average body weight and age: 15.85 kg and 4.5 months, respectively) were equitably divided in three homogenous groups and used for 90 days. Groups received respectively oat hay (Diet 1), dried olive leaves+ dried gueddim (D2) and khortane (D3). There were supplemented with 350 g of concentrate and received water twice a day. During the experimental period, animals were weighed every week until slaughter day. Live body weight (LBW) was higher (p<0.001) in D 2 (17.65 ± 1.61) compared to D1 and D3 (16.69 ±1.67 and 17.1 ± 1.56 kg respectively). The average dry matter intake was 488.82 ± 21.92; 619.23 ± 16.70 and 591.51 ± 23.08 respectively for D1, D2 and D3. Daily body gain (DBG) in D2 and D3 groups was comparable (35.2 and 34.4 g, respectively), but lower (P<0.0001) in D1 group (24.8 g). In conclusion, khortane, gueddim and dried olive leaves could efficiently substitute oat hay during fattening period of local goat kids.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)